دور الإعلام الجديد في تفعيل المشاركة السياسية - مقدم رقية (My University, 2018)
ملخص: يمكن لوسائل الإعلام الجديد أن تلعب دور كبير في عملية الإصلاح السياسي من خلال تعزيز المشاركة السياسية، التي تعتمد على التواصل مع الجماهير ، في ذلك الحين تشكل وسائل الإعلام الجديد أحد المداخل الأساسية لدراسة طبيعة العلاقة الموجودة بين الفرد والحكومة ويظهر ذلك جليا في الإصلاح السياسي وتفعيل المشاركة السياسية. مما يساعد الإعلام الجديد في دعم المشاركة السياسية باستخدام جملة تكنولوجيات الاتصال الحديثة، وهذا ما يدعو لتحقيق الهدف الرئيسي من كل هذا وهو تطبيق الديمقراطية. Summary: New media can play a major role in the political reform process by promoting political participation, which depends on communication with the masses. At the time, the new media constitute one of the main approaches to studying the nature of the relationship between the individual and the government. This is evident in political reform And activating political participation. Which helps the new media to support political participation using the latest technologies of communication, which calls for achieving the main objective of all this is the application of democracy
Keywords: الإعلام الجديد ; الانترنت ; المشاركة السياسية ; تفعيل المشاركة السياسية